2014
DOI: 10.2337/db13-0887
|View full text |Cite
|
Sign up to set email alerts
|

Osteocalcin Promotes β-Cell Proliferation During Development and Adulthood Through Gprc6a

Abstract: Expanding β-cell mass through β-cell proliferation is considered a potential therapeutic approach to treat β-cell failure in diabetic patients. A necessary step toward achieving this goal is to identify signaling pathways that regulate β-cell proliferation in vivo. Here we show that osteocalcin, a bone-derived hormone, regulates β-cell replication in a cyclin D1–dependent manner by signaling through the Gprc6a receptor expressed in these cells. Accordingly, mice lacking Gprc6a in the β-cell lineage only are gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
189
1
8

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 220 publications
(202 citation statements)
references
References 43 publications
4
189
1
8
Order By: Relevance
“…Recent emerging results from two independent laboratories have indicated that, in addition to Glut4, Glut1 is necessary for bone formation and whole-body glucose homoeostasis. Moreover, Glut1 is modulated by high glucose levels (Virta et al 2014, Wei et al 2014a. Collectively, these results provide a deeper understanding of the role of bone in the regulation of glucose metabolism (summarised in Fig.…”
Section: Glucose Transporter and Bonementioning
confidence: 88%
See 1 more Smart Citation
“…Recent emerging results from two independent laboratories have indicated that, in addition to Glut4, Glut1 is necessary for bone formation and whole-body glucose homoeostasis. Moreover, Glut1 is modulated by high glucose levels (Virta et al 2014, Wei et al 2014a. Collectively, these results provide a deeper understanding of the role of bone in the regulation of glucose metabolism (summarised in Fig.…”
Section: Glucose Transporter and Bonementioning
confidence: 88%
“…injection of OC failed to markedly stimulate ERK activity, thus having minor effects on circulating serum insulin levels, which were increased in WT mice exposed to the same treatment. GPRC6A has been shown to be integral in the promotion of b-cell proliferation during development and adulthood via OC, thus highlighting GPRC6A as an important receptor for skeletal-tissue-mediated energy regulation via the pancreas (Pi et al 2011, Wei et al 2014a. Most recently, Oury et al (2013) demonstrated that OC acts via a pancreas-bone-testis axis, such that OC-stimulated testosterone synthesis is positively regulated by insulin signalling in osteoblasts and is independent of luteinising hormone (LH).…”
Section: Male Fertility and The Discovery Of The Oc Receptormentioning
confidence: 99%
“…Według Wei i wsp. [1] może ona mieć wpływ na metabolizm glukozy, uwalnianie insuliny i stymulację insulinowrażliwości. Badania tych autorów wskazują na potencjalny wpływ osteokalcyny na stymulację proliferacji komórek beta trzustki zarówno w okresie okołoporodowym, jak i u dorosłych.…”
Section: Osteokalcyna I Osteoprotegeryna/ Rankl a Trzustkaunclassified
“…In this issue, Wei et al (18) show that pancreatic b-cell mass is controlled during development and adulthood by osteocalcin via its receptor Gprc6a. Recently, several observations have highlighted that bone, more than supporting tissue, is a real endocrine organ regulating various functions including glucose metabolism and energy expenditure.…”
mentioning
confidence: 99%